Leitura de estudo e conhecimento na formação inicial dos estudantes de pedagogia - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
This research work is part of a project called “reading-based study and knowledge in initial pedagogy student education”. The objective of the study is to investigate how reading articu-lates with knowledge and qualification, taking into account study and learning strategies of pedagogy students. For this investigation, we carried out theme-based studies (Theoretical Foundation) which deal with issues that are important support for the development of the pro-ject, such as, knowledge, university education and reading. Our work is based specially on Castello-Pereira (2003), Britto (2004; 2005; 2009), Silva (2010), Britto and Castilho (2009), who developed concepts such as: epistemological attitude: critic or instrumental, reading-based study, objective availability, concept of authorship and collection constitution, besides developing similar studies to ours. The above concepts are very important to perceive the way students study and the motivations that make them have certain behaviors before acquired knowledge. Due to the complexity of the subject, it was necessary to use a set of methods, such as questionnaire application to a broad numbers of students (142) and prospective dia-logue-based interviews with a group of four students. This research investigated students of two universities in Santarém: a public and a private one. The study results provide us with important evidences of the formative process and conceptions of learning and knowledge con-struction of pedagogy students. This research suggests that the students have a tendency to relate knowledge, study and learning to instrumental instruction. The epistemological atti-tudes pedagogy students continue to be that of regarding knowledge as something instrumen-tal, utilitarian that has pragmatics implications on the studying and learning forms.
Keywords: Conhecimento; Leitura e estudo; Estudar; Ensino Superior; CNPQ:: CIÊNCIAS HUMANAS::EDUCAÇÃO::ENSINO SUPERIOR::LEITURA; PRÁTICAS EDUCATIVAS, LINGUAGENS E TECNOLOGIAS; PRÁTICAS EDUCATIVAS, LINGUAGENS E TECNOLOGIAS